Low Pre-Treatment Count of Circulating Endothelial Progenitors as a Prognostic Biomarker of the High Risk of Breast Cancer Recurrence - Rhone, Piotr (J Clin Med, 2019)
Neoangiogenesis is mediated by circulating bone marrow-derived endothelial progenitors (circulating EPCs). The aim of the study was the quantification of circulating EPCs from the peripheral blood mononuclear cells of invasive breast cancer (IBrC) patients by flow cytometry, before and after cancer adjuvant treatment. A total of 88 stage IA-IIB primary IBrC patients were enrolled prospectively. Circulating EPCs with the immune-phenotype CD45−CD34+CD133+CD31+ were assessed. Treatment significantly reduced the number of EPCs/µL in the general IBrC cohort. However, there was a relevant elevation in the number of circulating EPCs after nine months of adjuvant treatment in the group of patients aged ≥ 55 years, of T2 clinical type, with nodal involvement (N1) and Ki67 expression > 15%. Follow-up revealed a significantly higher incidence of disease relapse in breast cancer patients with low pre-treatment circulating EPCs levels compared with those with a high baseline circulating EPCs count. The receiver-operating characteristic curve identified a tumour diameter of 2.1 cm as the best cut-off value to discriminate between disease-relapse subjects and non-relapse disease cases. Our study strongly indicates that, next to tumour diameter and Ki67 expression, circulating bone marrow-derived EPCs may serve as useful markers for predicting therapeutic outcomes as well as a future prognosis.